Transition from cutaneous into mucocutaneous pemphigus vulgaris – case report and review of literature - Sar-Pomian, Marta; Glińska-Wielochowska, Maria; Szewczyk, Agnieszka; Kraińska, Teresa; Kołacińska-Strasz, Zofia; Sulej, Jadwiga; Łabęcka, Hanna; Gliński, Wiesław; Olszewska, Małgorzata (Dermatology Review/Przegląd Dermatologiczny, 2009)
Introduction: The clinical, histological and immunological profile of cutaneous pemphigus vulgaris may show significant differences between individual patients. In most cases the clinical appearance is characteristic for pemphigus foliaceus. Histopathology shows deep acantholysis and immunological profile reveals a higher level of anti-Dsg1 antibodies in comparison with anti-Dsg3 antibodies. Objective: Presentation of an unusual case of pemphigus vulgaris in which transition from cutaneous into mucocutaneous type of disease was observed. Case report: A 52-year old woman presented with bullous lesions on the trunk. Histopathological examination revealed acantholysis in suprabasal localization. Direct immunofluorescence demonstrated intercellular IgG and C3 deposits. Indirect immunofluorescence revealed circulating pemphigus autoantibodies in equal titres of 320 on monkey and on guinea pig oesophagus. ELISA showed antibody indices anti-Dsg1 and anti-Dsg3 of 121 and 54 respectively. Cutaneous pemphigus vulgaris was diagnosed. Remission occurred after treatment with prednisone. Two years later, new lesions on skin and oral mucosa occurred. Histopathological examination revealed deep acantholysis. ELISA showed anti-Dsg1 index of 59, anti-Dsg3 of over 150. These results permitted diagnosis of mucocutaneous pemphigus vulgaris. Conclusions: We present an unusual case of a patient with cutaneous pemphigus vulgaris evolving into mucocutaneous form of the disease.